Portugal: As condições territoriais de um processo de terciarização vulnerável - Ferrão, João; Domingues, Álvaro (Finisterra, 1994)
Portugal: The territorial foundations of a vulnerable tertiarization - This paper aims at identifying the reasons for the recent growth of producer services in Portugal, having in mind the existence of different territorial models of development.In the introduction, both the dynamism and the vulnerability of the recent growth of producer services are underlined. In the first section, the heavily polarized geography of producer services in Portugal is described. In the second section, the situations of the two main service agglomerations -Lisbon and Oporto- are evaluated. In the final summing-up, the existence of three distict issues associated to the three kinds of territorial realities is suggested: non-industrialized areas with marked specialization; urban agglomerations with a "eurocity" profile. Lastly adjustement of service policies to each of these territorial realities is considered a crucial factor for successful practices.